2018
DOI: 10.2478/folmed-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Analgesic Effect of the Antidepressant Escitalopram

Abstract: Background: Antidepressants have been found to possess antinociceptive and analgesic properties and are prescribed in the treatment of chronic pain. Aim: To evaluate the antinociceptive properties of escitalopram after a single administration. Materials and methods: Forty Wistar rats were used in the study. They were divided into 5 groups (n=8) treated with saline solution (control group), metamizole (150 mg/kg b.w.), escitalopram (5, 10 and 20 mg/kg b.w.) intraperitoneally. The nociceptive tests we used emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The doses of escitalopram used in this study were chosen on the basis of preliminary experiments in depression and colitis rat models which had shown reasonable safety and efficacy 25,26 …”
Section: Methodsmentioning
confidence: 99%
“…The doses of escitalopram used in this study were chosen on the basis of preliminary experiments in depression and colitis rat models which had shown reasonable safety and efficacy 25,26 …”
Section: Methodsmentioning
confidence: 99%
“…Although comorbid pain and depression have long been recognized, their foundations are complex. Experimental studies have found that antidepressants have antinociceptive and analgesic effects, and therefore, they can be used in combination to treat chronic pain [ 149 ]. Most studies have focused on the HPA, neuroinflammatory factors, neurogenesis, glutamate, GABA, and various neurotransmitters and neuromodulators.…”
Section: Antidepressants As Antinociceptive Drugs In Animal Models Of...mentioning
confidence: 99%
“…In these rodent models, SSRI (escitalopram) induced antinociception. However, other studies in mice indicated that escitalopram does not have analgesic activity at low doses but induces a weak antinociceptive effect at extremely high doses (150 and 200 mg/kg body weight) [ 149 ]. In addition, contradictory results were obtained for the effectiveness of fluoxetine in similar thermal, chemical, electrical, and inflammatory pain models [ 100 ].…”
Section: Antidepressants As Antinociceptive Drugs In Animal Models Of...mentioning
confidence: 99%
“…6,7 ET has serious side effects such as nausea, dry mouth, sleep disturbance, constipation, fatigue, drowsiness, and dizziness, resulting in patients needing to gradually increase the therapeutic dose. 6,7 ET has serious side effects such as nausea, dry mouth, sleep disturbance, constipation, fatigue, drowsiness, and dizziness, resulting in patients needing to gradually increase the therapeutic dose.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used escitalopram (ET), an antidepressant, which is a selective serotonin reuptake inhibitor in the brain cells . ET has serious side effects such as nausea, dry mouth, sleep disturbance, constipation, fatigue, drowsiness, and dizziness, resulting in patients needing to gradually increase the therapeutic dose .…”
Section: Introductionmentioning
confidence: 99%